Could the Clinical Effectiveness Be Improved Under the Integration of Orthotic Intervention and Scoliosis-Specific Exercise in Managing Adolescent Idiopathic Scoliosis?: A Randomized Controlled Trial Study. (August 2019) - Gao, Chengfei; Zheng, Yu; Fan, Chunjiang; Yang, Yan; He, Chengqi; Wong, Mansang
Abstract : Objective: The aim of the study was to compare the effectiveness of the integration of orthotic intervention and scoliosis-specific exercise with orthotic intervention only via assessing the spinal deformity, back muscle endurance, and pulmonary function of the patients with adolescent idiopathic scoliosis. Design: It is a prospective randomized controlled study. Patients who fulfilled the SRS criteria for orthotic intervention were randomly assigned to the orthosis combined with exercise group (combined orthotic and exercise intervention) or the orthotic intervention group (orthotic intervention only). All the subjects were prescribed with a rigid thoracolumbosacral orthosis and scoliosis-specific exercise program was provided to the subjects in the orthosis combined with exercise group. Cobb angle, back muscle endurance, and pulmonary function of subjects were measured at baseline, 1-mo, and 6-mo follow-up visits. Results: After 6 mos of intervention, the subjects in the orthosis combined with exercise group showed better Cobb angle correction than those in the orthotic intervention group. The back muscle endurance and pulmonary function decreased in the subjects of the orthotic intervention group, whereas some improvement happened in the subjects of the orthosis combined with exercise group. Between-group statistical significance was detected at the 6-mo follow-up among back muscle endurance time and parameters of pulmonary function. Conclusions: In this study, orthotic intervention combined with scoliosis-specific exercise offered better Cobb angle correction and improvement of the respiratory parameters and back muscle endurance of the patients with adolescent idiopathic scoliosis as compared with orthotic intervention only. Abstract : Supplemental digital content is available in the text.